Friendly fire - the trade impact of the Russia sanctions and counter-sanctions - Matthieu Crozet; Julian Hinz (Kiel Institute for the World Economy (IfW), 2016)
Economic sanctions are a frequent instrument of foreign policy. In a diplomatic conflict, they aim to elicit a change in the policies of foreign governments by damaging their economy. However, sanctions are not costless for the sending economy, where domestic firms involved in business with the target countries might incur economic damages. This paper evaluates these costs in terms of export losses of the diplomatic crisis that started in 2014 between the Russian Federation and 37 countries, (including the United States, the EU, and Japan) over the Ukrainian conflict for the implicated countries. We first gauge the impact of the sanctions' regime using a structural gravity framework and quantify the trade losses in a general equilibrium counterfactual analysis. We estimate this loss at US114 billion from 2014 until the end of 2015, with US 44 billion being borne by sanctioning Western countries. Interestingly, we find that the bulk of the impact stems from products that are not directly targeted by Russian retaliations (taking the form of an embargo on imports of agricultural products). This result suggests that most of the losses are not attributable to the Russian retaliation but to Western sanctions. We then investigate the underlying mechanism at the firm level using French customs data. Results indicate that neither consumer boycotts nor perceived country risk can account for the decline in exports of products that are not targeted by the Russian embargo. Instead, the disruption of the provision of trade finance services is found to have played an important role.
Keywords: F51; F14; F13; F52; 330; Sanctions; Trade; Foreign policy; Boycott; Embargo; Trade finance